Phase II trial in adults of concurrent or sequential 2009 pandemic H1N1 and 2009–2010 seasonal trivalent influenza vaccinations. Issue 1 (1st January 2015) - Frey, Sharon E.; Bernstein, David I.; Brady, Rebecca C.; Keitel, Wendy A.; Sahly, Hana El; Rouphael, Nadine Georges; Mulligan, Mark J.; Atmar, Robert L.; Edupuganti, Srilatha; Patel, Shital M.; Dickey, Michelle; Graham, Irene; et al.
Abstract: Background: During the 2009 influenza pandemic both seasonal and 2009 pandemic vaccines were recommended. We conducted a randomized trial of monovalent 2009-H1N1 vaccine and seasonal trivalent inactivated influenza vaccine (IIV3) given sequentially or concurrently to adults. Methods: Adults randomized to 4 study groups and stratified by age (18–64 and ≥65 years) received 1 dose of seasonal IIV3 or placebo and 2 doses of 2009-H1N1 vaccine or placebo in one of 4 combinations, i.e., H1N1 + Placebo/H1N1 + Placebo/II V 3 (HP/HP/V3 ), H1N1 + IIV3 /H1N1 + Placebo/Placebo (HV3 /HP/P), H1N1 + Placebo/H1N1 + IIV3 /Placebo (HP/HV3 /P), andIIV3 + Placebo/H1N1 + Placebo/H1N1 (V3 P/HP/H). Intramuscular injections were given three times at 21 day intervals. Sera for antibody assays were obtained prior to and 21 days after each vaccination. Reactogenicity and adverse events were monitored. Results: Eight hundred-five (805) adults were enrolled. All combinations of vaccines were safe and well tolerated. In general, one dose of 2009-H1N1 and one dose of IIV3, regardless of sequence or concurrency of administration, were immunogenic in adults. There were no significant differences in geometric mean titers (GMT) or the proportions of subjects with ≥4-fold rise in antibody responses and titers ≥40 for any vaccine group or between age strata for 2009-H1N1 after the first or second dose, although the vaccine sequence affected the titers to the IIV3 antigens. Hemagglutination inhibition antibody (HAI) GMTs against 2009-H1N1 for the combined age strata 21 days after the first 2009-H1N1 dose were 190.4, 182.1, 232.9 and 157.5 for HP/HP/V3, HV3 /HP/P, HP/HV3 /P andV3 P/HP/H, respectively. While IIV3 GMTs were adequate they were generally lower than the 2009-H1N1 GMTs. In a subset of subjects, there was good correlation between HAI and microneutralization (MN) titers (Spearman's correlation coefficient 0.92). Conclusions: All vaccine combinations were generally well tolerated. Immune responses to one dose of 2009-H1N1 were adequate regardless of the sequence of vaccination in all age groups, but the sequence affected titers to IIV3 antigens.